How to develop and manage your own community seed bank. Farmers’ handbook (Booklet 1 of 3). [Nuer version] - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Dibiloane, Angeline; Lettie Maluleke, Nkat; Abner Matelele, Lehlogonolo; Mokoena, Mpolokeng Lydia; Phora, George; Sema, Precious; Thabo, Tjikana (2021)
Nuer edition of: Vernooy, R.; Bessette, G.; Sthapit, S.; Dibiloane, A.; Lettie Maluleke, N.; Abner Matelele, L.; Mokoena, M.; Phora, G.; Sema, P.; Thabo, T. (2018) How to develop and manage your own community seed bank: Farmers’ handbook. Establishing a community seed bank: Booklet 1 of 3. This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). Booklet 2 of 3 can be found here: https://hdl.handle.net/10568/117467. Booklet 3 of 3 can be found here https://hdl.handle.net/10568/117470. The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Translation and adaptation to the local language is encouraged. If you would like to receive a hard copy of the booklets or give feedback or suggestions for improvement, please contact r.vernooy@cgiar.org.